Gain Performance of GeSn based n-p-n Heterojunction Phototransistor - Pandey, Ankit Kumar; Basu, Rikmantra; Chang, Guo-En (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
A n-p-n heterojunction phototransitor with Ge 1-x Sn x base is presented. The work is focussed on effect of Sn concentration on the gain performance of the device based on optimised base and collector doping.